EFFECT OF ROA, NPM, CR, EPS ON STOCK PRICES IN CONSUMER GOODS COMPANIES - Herlina Novita; Michael Pratama Surbakti; Fitri Yanti Manalu; Kristina Eva Yanti Silalahi; Rany Hezellyta Bukit (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study aims to determine the effect of ROA, NPM, CR, and EPS simultaneously and partially on stock prices in consumer goods companies listed on the IDX for the period 2017 – 2020. This study uses a population of 53 consumer goods companies listed on the IDX for the 2017period – 2020. The method used in this study is a quantitative method. The data used are secondary data registered through the official website www.idx.co.id and www.idn.financials.com. In this study, the sample was taken using purposive sampling technique. This research was tested using the classical assumption test. The data investigation method used was the multiple linear regression method. The results showed that partially ROA, CR, and EPS had a significant effect on stock prices partially and NPM had a positive and significant effect on stock prices. IDX for the period 2017 – 2020.